HIV-1 tat protein stimulates transcription by binding to a U-rich bulge in the stem of the TAR RNA structure. - Dingwall, C (1990)
The HIV-1 trans-activator protein, tat, is an RNA binding protein with a high affinity for a U-rich bulge near the tip of the stem in the RNA stem-loop structure encoded by the trans-activation responsive region (TAR). A Scatchard analysis of tat binding has shown that the purified protein forms a one-to-one complex with HIV-1 TAR RNA with a dissociation constant of Kd = 12 nM. Deletion of the uridine residues in the bulge or substitution with guanine residues produced RNAs with a 6- to 8-fold lower affinity than wild-type TAR. Introduction of a point mutation expected to destabilize base pairing in nearby residues of the TAR stem-loop structure reduced tat binding 10-fold. In contrast, mutations that alter the sequence of the six nucleotide long loop at the tip of TAR RNA structure, and mutations which alter the sequence of the stem whilst preserving Watson-Crick base pairing, do not affect tat binding significantly. There is a direct correlation between the ability of tat to bind to TAR RNA and to activate HIV transcription. Viral LTRs carrying TAR sequences encoding any of the mutations known to produce transcripts which bind tat weakly, are not stimulated efficiently by tat in vivo.